Fetal Cell Microchimerism; Normal and Immunocompromised Gestations in Mice. (3rd July 2020) - Beksac, M. Sinan; Fadiloglu, Erdem; Cakar, Ayse Nur; Gurbuz, Rumeysa Hekimoglu; Atilla, Pergin; Onbasilar, Ilyas; Beksac, Kemal; Katlan, Doruk Cevdi; Mumusoglu, Sezcan; Calis, Pinar; Beksac, Meral
Abstract: Objective: To compare fetal cell microchimerism in normal and immunocompromised gestations. Materials and methods: The study consists of two groups of mature female mice. In the control group and the immunocompromised study group, 5 mg of saline and cyclosporine were injected intraperitoneally, respectively. In the second step, all female mice were mated with "Actine-Luc (+) green fluorescent protein (GFP)" transgenic male mice. Immunohistochemical studies (ALPL-antiluciferase, cytokeratin-antiluciferase, and CD 105-antiluciferase) were carried out on maternal liver, skin, and lung tissues at 6–7th and 14–15th gestational days, and postpartum 3–4th, 12th, and 18–24 months. Results: GFP (+) cells were detected in maternal liver and skin but not in lung tissue. Liver was the most affected tissue. GFP was found to be more intense in the immunocompromised group. Conclusion: Fetal microchimerism was demonstrated in maternal liver and skin and found to be more intensive in the immunocompromised group.